2017
DOI: 10.1186/s12876-016-0560-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of body weight with gastrointestinal motor and sensory function: studies in anorexia nervosa and obesity

Abstract: BackgroundWhether gastrointestinal motor and sensory function is primary cause or secondary effect of abnormal body weight is uncertain. Moreover, studies relating continuous postprandial sensations of satiation to measurable pathology are scarce. This work assessed postprandial gastrointestinal function and concurrent sensations of satiation across a wide range of body weight and after weight change.MethodsPatients with anorexia nervosa (AN) and obesity (OB) were investigated in reference to normal weight con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 79 publications
4
81
1
Order By: Relevance
“…This result suggests that gastric emptying is delayed in ABA mice mainly due to malnutrition. These data are in accordance with previous studies reporting that gastric emptying was normalized after weight restoration in AN patients . However, 2 studies also showed that gastric emptying remained delayed after refeeding .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result suggests that gastric emptying is delayed in ABA mice mainly due to malnutrition. These data are in accordance with previous studies reporting that gastric emptying was normalized after weight restoration in AN patients . However, 2 studies also showed that gastric emptying remained delayed after refeeding .…”
Section: Discussionsupporting
confidence: 93%
“…34 To our in accordance with previous studies reporting that gastric emptying was normalized after weight restoration in AN patients. [7][8][9] However, 2 studies also showed that gastric emptying remained delayed after refeeding. 10,11 In our study, we did not evaluate gastric emptying after refeeding in LFA and ABA mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study described that from 30 patients diagnosed with primary AN, seven were mistakenly diagnosed and suffered from achalasia instead, indicating that esophageal dysmotility can be misjudged as AN (Stacher et al, 1986). In contrast to gastric dysmotility, esophageal dysmotility (Bozzato et al, 2008;Günther, 1988;Hasler, 1982;Mignogna, Fedele, & Lo Russo, 2004;Price et al, 2008;Walsh et al, 1981;Willershausen, Philipp, Pirke, & Fichter, 1990) Oral health impairment -Vomiting behaviour (Johansson et al, 2012;Touyz et al, 1993) Esophageal dysmotility -Vomiting behaviour ➔ esophageal damage ➔ dysfunction of neural regulation (Benini et al, 2010;Holmes et al, 2012;Stacher et al, 1986) Esophageal cancer -Vomiting behaviour (Brewster et al, 2015;Pacciardi, Cargioli, & Mauri, 2015) Impaired gastric dysmotility -Food restriction, laxative abuse ➔ gastric damage including autonomic nerve dysfunction ➔ dysfunction of neural regulation ➔ bradygastria (Abell et al, 1987;Benini et al, 2004;Bluemel et al, 2017;Domstad et al, 1987;Diamanti et al, 2003;Dubois et al, 1979;Holt et al, 1981;Hutson & Wald, 1990;McCallum et al, 1985;Ogawa et al, 2004;Perez et al, 2013;Ravelli et al, 1993;Rigaud et al, 1988;Robinson, 1989;Robinson et al, 1988;Robinson & Stephenson, 1990;Stacher et al, 1992;Szmukler et al, 1990) Gastric dilatation -Reversible dysfunction of neural regulation ➔ decreased gastric motility and de...…”
Section: Esophageal Motilitymentioning
confidence: 99%
“…Associated with disordered gastric motility in AN, further symptoms were reported: increased incidence of gastric dysrhythmia (during fasting, AN: 9.75% vs. controls: 0.48%) and reduced antral contractility (mean motility index, AN: 12.8 vs. controls: 14.2;Abell et al, 1987) with reduced antral contraction amplitudes (Stacher et al, 1992) and increased self-reported postprandial fullness (Bluemel et al, 2017). Typical upper GI symptoms such as nausea, vomiting, and gastric fullness were observed to correlate with delayed emptying (Rigaud et al, 1988), whereas satiety (Robinson, 1989) and body weight (Hutson & Wald, 1990) did not show any correlation with gastric emptying.…”
Section: Alterationmentioning
confidence: 99%